Comparative Analysis of Different Disinfection Techniques Performances in Drinking Water Treatment Plant Using a Process Simulation Software - Hayder Mohammed Issa (Zanco Journal of Pure and Applied Sciences, 2019)
The performance of chlorination disinfection in drinking water treatment is facing challenges with the potentiality to produce disinfection by-products. Seeking safer drinking water quality is related to increasing demands by consumers who are looking for better assurances about the quality of the water they drink. In this study, a water treatment process simulator of WatPro 4.0 was used under certain influent conditions to evaluate possibilities for alternating an existing chlorination disinfection process in a drinking water treatment plant (DWTP-Efraz 2) in March 2014 at Erbil, North Iraq. The evaluation was made in terms of effluent water quality and disinfection by-products formation potentials. The studied disinfection processes are; chlorination, ozonation, and ultraviolet. In the chlorination process simulation, the predicted effluent water quality was verified by the analysis and testing results of the effluent treated water goes out from the plant (Efraz-2). Results showed that each of the studied disinfection processes has its own environmental and limitation pros and cons. Ultraviolet disinfection process meets the required standards of the lowest potential of disinfection by-products. Ozonation included a lower risk than chlorination in the formation of disinfection by-products from the dissolved organic matter. The other parameters of water quality showed close characteristics for all the three disinfection processes. The results obtained in this work gives further insight into the performance of water treatment plant design and encourage the application of water treatment simulators as tools for disinfection process development.